The Use of Indonesian Language Rules in Scientific Articles of UIN Raden Intan Lampung Lecturer - Dedi Satriawan (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Research scientific articles are made using language as a tool. Therefore, lecturers as writers must understand and implement language rules. Both in terms of the use of spelling, diction, effective sentences, and paragraphs. The formulation of the problem in this study is how the form of errors in the use of spelling, diction, effective sentences, and paragraphs in the scientific articles of UIN Raden Intan Lampung lecturers for the 2021 Fiscal Year. Related to this, this study aims to describe the forms and number of errors in the use of Indonesian language rules in a scientific article by a lecturer at UIN Raden Intan Lampung for the 2021 Fiscal Year. The method used in this research is qualitative. Data were taken from 48 scientific articles researched by UIN Raden Intan Lampung lecturers for the 2021 Fiscal Year. The results showed that there were 537 errors in the use of Indonesian language rules in the research articles by UIN Raden Intan Lampung Lecturers for the 2021 Fiscal Year. The details are 1) 247 spelling errors, which include: errors in the use of capital letters, errors in prepositions in and to, errors in the use of punctuation marks, and errors in writing absorption elements; 2) there were 215 errors found related to diction; 3) there are 67 errors found related to effective sentences; and 4) there were 8 errors found related to paragraphs.